2018
DOI: 10.1007/s00227-018-3321-3
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification and desalination: climate-driven change in a Baltic Sea summer microplanktonic community

Abstract: Helcom scenario modelling suggests that the Baltic Sea, one of the largest brackish-water bodies in the world, could expect increased precipitation (decreased salinity) and increased concentration of atmospheric CO2 over the next 100 years. These changes are expected to affect the microplanktonic food web, and thereby nutrient and carbon cycling, in a complex and possibly synergistic manner. In the Baltic Proper, the extensive summer blooms dominated by the filamentous cyanobacteria Aphanizomenon sp., Dolichos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 73 publications
5
27
0
Order By: Relevance
“…Nevertheless, no effects of elevated pCO 2 were found on the filamentous cyanobacteria. These results are consistent with some previous studies (Paul et al 2016, Wulff et al 2018, while others show increased growth (Wannicke et al 2012, Eichner et al 2014. Also, filamentous cyanobacteria are known to cope with daily fluctuations in pH measured both in aggregates (Ploug 2008) and in situ conditions (Wulff et al 2018).…”
Section: Response Of Filamentous Cyanobacteria To Elevated Temperatursupporting
confidence: 93%
See 3 more Smart Citations
“…Nevertheless, no effects of elevated pCO 2 were found on the filamentous cyanobacteria. These results are consistent with some previous studies (Paul et al 2016, Wulff et al 2018, while others show increased growth (Wannicke et al 2012, Eichner et al 2014. Also, filamentous cyanobacteria are known to cope with daily fluctuations in pH measured both in aggregates (Ploug 2008) and in situ conditions (Wulff et al 2018).…”
Section: Response Of Filamentous Cyanobacteria To Elevated Temperatursupporting
confidence: 93%
“…The biovolume of Aphanizomenon sp. decreased at the initiation of the experiment, as also observed by Wulff et al (2018), thus, no temperature effects could be observed.…”
Section: Response Of Filamentous Cyanobacteria To Elevated Temperatursupporting
confidence: 72%
See 2 more Smart Citations
“…The likely combined biological effects of this freshening with OA in the Baltic-Skagerrak System have received relatively little attention to date. Available data indicate increased sensitivity to OA in low-salinity populations (crustaceans, Gulf of Bothnia, Wood et al 2016 ), potential for freshening to counteract the positive effects of OA on reproductive success ( Fucus , Baltic, Serraõ et al Serrao et al 1999 ; Graiff et al 2017 ), and no substantive impacts of OA + freshening on microplankton community structure (Baltic Proper, Wulff et al 2018 ; Table 1 ). This important research area requires further experimental investigation before patterns in responses to this interaction can be identified.…”
Section: Interactive Effects Of Ocean Acidification: Species-level Rementioning
confidence: 99%